Analysis of age, stature, body mass, BMI and quality of elite soccer players from 4 European Leagues - Bloomfield, J.; Polman, R.; Butterly, R.; O'Donoghue, P. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The aim was to identify which league (English Premier League, Spanish La Liga Division, Italian Serie A and German Bundesliga) contained the highest quality players and whether differences in age, stature, body mass and BMI existed between the different positions in different leagues. Methods: Data were collected concerning 2 085 professional soccer players playing in these 4 leagues during the 2001-2002 season. Player quality was determined by the leagues¹ number of international players and their nations¹ FIFA World Ranking (FWR). Results: The La Liga Division contained the highest quality players (mean FWR) (11.5±13.8), followed by the Serie A (13.3±21.3), the Premier League (30.6±27.3) and the Bundesliga (30.7±27.1), respectively. Also, differences were found between the age, stature, body mass and BMI of players in different positions and in the different leagues. Age had a significant influence on position with goalkeepers (years) (27.4±5.3) being older than midfielders (26.2±4.3) and forwards (25.8±4.2) and defenders (26.8±4.3) being older than forwards. Players from the Bundesliga had the greatest stature (m) (1.83±0.06), body mass (kg) (77.5±6.4) and BMI (kg . m-2) (23.2±1.1) of the 4 leagues. In reflection, La Liga¹s players had the shortest stature (1.80±0.06) and the Serie A players had the least body mass (74.3±5.4) and BMI (22.8±1.1). Conclusion: The differences discovered suggest either differences in playing style and physical demands of the different leagues, different physical conditioning methods or, alternatively, that there are desirable characteristics of players with teams in all 4 leagues seeking such players.